Analysis of Vibration in Pipe: Effect from Different Pipe Sizes and Pressure Inlet - Willy, Matilda Stacia; Mohd Salleh, Zuliazura (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Pipe vibration is a common problem in industries, causing damage and safety concerns. This study investigates how pressure loss in pipes leads to vibrations. When fluid flows through pipes, friction causes pressure to drop and speed to increase, resulting in damaging vibrations. The research focuses on the UTHM Biodiesel Plant’s pipeline, analysing the pressure drop from the air compressor to the reservoir tank. The study examines the impact of different pipe sizes (Model 1: 65 mm, Model 2: 80 mm, Model 3: 105 mm) and pressure levels (6 bar, 8 bar, 10 bar) on the pressure drop. Using SOLIDWORKS and ANSYS software for design and simulation, a 3D model of the pipes serves as a reference. The objective is to identify the model with the least pressure drop, aiming to minimise vibrations in the pipeline. By understanding how varying diameter sizes and pressure levels affect pressure drop, this research seeks to provide insights for mitigating pipe vibrations. This study aims to bring about improvements in pipeline systems that positively impact both structural integrity and overall operational effectiveness. The larger diameter pipe is observed to potentially contribute to reduced vibrations in the pipeline. The larger the diameter of the pipes, the lower the pressure drop in the pipeline. This is because pipes with larger diameters have lower pressure drops, higher velocities, and increased temperatures. In other words, the larger the diameter of the pipe, the lower the pressure drop in the pipeline.